Study on the isolation of rhizosphere bacteria and the mechanism of growth promotion in winter wheat in response to drought stress - Zhang, Lijuan; Pan, Yanshuo; Qi, Yanjie; Bai, Jing; Han, Dongfei (Frontiers in Plant Science, 2025)
IntroductionWheat is one of the three major cereal crops in the world and is susceptible to the effects of drought stress. Rhizosphere microorganisms can affect plant growth by altering nutrient absorption and resistance to stress. Studying the plant–microbe interaction under drought stress to reveal the impact of soil microorganisms on plant growth in dry land has important scientific significance.MethodsIn this study, seven plant growth-promoting bacteria were isolated from the rhizosphere soil of winter wheat, and their growth-promoting ability was compared and analyzed.ResultsThe results indicate that these strains are capable of hydrolyzing organic and inorganic phosphorus, fixing nitrogen, producing IAA (indole-3-acetic acid), ACC deaminase, and iron siderophore. Combined with pot experiment data, Microbacterium sp. I2, Arthrobacter sp. R4, and Microbacterium sp. K2 can significantly promote wheat growth. Under normal conditions, the wheat plant height increased by 5.17%, 13.02%, and 12.14% compared to the control group after one month of treatment with I2, R4, and K2, respectively. Under drought stress, the plant height increased by 6.41%, 2.56%, and -3.46%, respectively. However, under drought stress, only K2 significantly increased wheat root length by 11.94% compared to the control group. Therefore, K2 has stronger drought resistance than I2 and R4. Genome sequencing and comparative genome analysis of I2, R4, and K2 strains revealed that the strains contain functional gene clusters related to phosphorus solubilization (pstABCS, phoUR), ACC deamination (accABD), iron transport (fepCDG), IAA production (trpABC), nitrogen fixation (nifUHJ), drought resistance (ostAB, treXYZ), but with different gene types and copy numbers. Compared to I2, the R4 genome lacks one copy of the phoUR gene cluster, ACC deaminase, and iron transport related functional gene clusters. The K2 genome contains both treXYZ and ostAB gene clusters, which may be associated with its significant improvement in plant drought resistance.DiscussionThis study indicates that PGPB may promote plant growth by affecting nutrient absorption and hormone synthesis, while also affecting plant drought resistance by regulating osmotic pressure and trehalose biosynthesis, providing a theoretical basis for regulation of plant growth in a sustainable way.